Upaya Guru Pendidikan Agama Islam Dalam Membina Akhlak Siswa Di Sekolah Menengah Pertama Plus Al-Barokah Babat Lamongan - Jauhari, Imam; Amirudin, noor; Ladamay, Man Arfa' (STIT Muhammadiyah Paciran, 2021)
The study and discussion of this thesis aims to describe the efforts made by Islamic religious education teachers in fostering the morals of the students of SMP Plus Al Barokah Babat Lamongan. In order to achieve this goal, the researchers used a literature approach and empirical studies/field research. This type of research is a descriptive qualitative research. The subjects of this thesis research are: Principals, Islamic Religious Education Teachers, student representatives and other informants related to the issues discussed. This qualitative research method uses three data collection techniques, namely: a) Observation, b) Interview, and c) Documentation. The results of the study show that: 1) the efforts made by Islamic religious education teachers in fostering student morals are: a) providing knowledge about morals, b) good habits, c) giving advice, d) giving punishment to students who violate the rules, e) being a good role model, f) cooperating with parents, g) enforcing discipline, h) giving direction and motivation.